Ability tracking and social capital in China's rural secondary school system - Fan Li; Prashant Loyalka; Hongmei Yi; Yaojiang Shi; Natalie Johnson; Scott Rozelle (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
The goal of this paper is describe and analyze the relationship between ability tracking and student social capital, in the context of poor students in developing countries. Drawing on the results from a longitudinal study among 1,436 poor students across 132 schools in rural China, we find a significant lack of interpersonal trust and confidence in public institutions among poor rural young adults. We also find that there is a strong correlation between ability tracking during junior high school and levels of social capital. The disparities might serve to further widen the gap between the relatively privileged students who are staying in school and the less privileged students who are dropping out of school. This result suggests that making high school accessible to more students would improve social capital in the general population.
Keywords: 330; Ability Tracking; Social Capital; Interpersonal Trust; Confidence in Public Institutions; Rural Secondary Schooling